To årstal. Replik - Thaning, Kaj (Grundtvig-studier, 1991)
Two Years. A Reply By Kaj Thaning. Recently a collection of essays by Anders Pontoppidan Thyssen has been under the title ‘ Grundtvig and the Grundtvigian Heritage’. One of the articles is a reprint of A.P. Thyssen’s critical examination of K. Thaning’s thesis .Menneske f.rst Grundtvigs opg.r med sig selv., (1963). In his article Thyssen has opposed Thaning’s views that the year 1832 should be seen as the decisive turning point in Grundtvig’s life. This view caused an extensive debate, in the course of which Thaning also wrote a rejoinder to Thyssen and other critics. In the present short contribution Kaj Thaning reconsiders his point of view.